El rol de los docentes co-formadores en el proceso de prácticas del Profesorado en Historia - Verónica Gatti; Marcela Zatti; Martín Céparo (Clio y Asociados, 2019)
In the teaching career in History of the Autonomous University of Entre Ríos, the teaching practices are carried out at secondary and higher levels, so we are interested in observing, analyzing and understanding the processes that involve the practicing students in the diagramming and preparation of the classes during their initial training, that is, the decisions that are made and are assumed when planning the teaching sequences within the framework of the Didactics of History and Social Sciences and the Educational Action Workshop. In this sense, we have previously worked with the narratives written by students in which various problems are reflected when it comes to giving account of the formulation of didactic proposal, group management, positioning of the teaching role, among others, unveiling a spectrum very broad about their experiences, bringing to light strengths and weaknesses. In order to make this line of inquiry more complex, we have decided in this opportunity to work on and analyze narratives provided by co-trainer teachers. Through an interview of methodological approach to the field of study, we introduce ourselves in the point of view of actors that have an important role in the process of the practices since they give us information from their concrete experience with our practitioners, allowing us to review teaching processes.